Social Networks as a Mean for Enforcing of the Employers Brand - Mironova, Nadia; Kicheva, Tatyana (Research Papers, 2018)
Building and enforcing a strong employer brand is one of the latest challenges faced by human resource management and development professionals and organizational leaders over the past few years. The purpose of this paper is to highlight the role of social networks as an effective mean of communicating and successfully enforcing the organization’s employer’s brand.. To achieve this goal, the concept of the employer brand, the process of its construction and its importance for attracting and retaining talents in the organization are analyzed from a theoretical point of view. Emphasis has been put on the use of social networks as a means of communicating and enforcing the employer brand. The results of the research conducted among the students of the specialty Business Administration specializing in Business Communications were analyzed in their role as talented potential future employees in the Bulgarian organizations. The results of the survey show student’s perception of the employer brand as a mean of attracting talents and their preferred communication channels to search for information about the organization and its employer when applying for a job.